2021
DOI: 10.15537/smj.2021.2.25693
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 deficiency in patients with type 2 diabetes mellitus using metformin and the associated factors in Saudi Arabia

Abstract: To assess the presence of vitamin B12 deficiency among metformin users and associated factors in patients with type 2 diabetes mellitus. Methods: An observational cross-sectional study was conducted with 307 diabetic patients in the primary health care centers at King Abdulaziz Medical City (KAMC), Riyadh, Saudi Arabia between October 2017 and January 2018. Face-to-face interviews were conducted with the participants, using a designed checklist. Results: The prevalence of vitamin B12 deficiency was (3.6%) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…This suggests that as age, FBG and HbA1c levels increase, vitamin B12 levels decrease. These findings are consistent with those of a study by Appold et al 20 which attributed the correlation to malnutrition in older adults. However, they contrast with the results of a study by Alsaeed 21 which found a positive correlation, likely due to the inclusion of patients receiving vitamin B12 supplements.…”
Section: Resultssupporting
confidence: 93%
“…This suggests that as age, FBG and HbA1c levels increase, vitamin B12 levels decrease. These findings are consistent with those of a study by Appold et al 20 which attributed the correlation to malnutrition in older adults. However, they contrast with the results of a study by Alsaeed 21 which found a positive correlation, likely due to the inclusion of patients receiving vitamin B12 supplements.…”
Section: Resultssupporting
confidence: 93%
“…Since 1971, when malabsorption of vitamin B12 in diabetic patients with metformin was first reported, 80 numerous clinical trials and meta‐analyses have confirmed the association between metformin and low vitamin B12 levels. 81 , 82 , 83 , 84 , 85 , 86 , 87 Vitamin B12 is found in foods as a protein‐binding form and released under the action of gastric acid pepsin and trypsin after entering the digestive tract. Then the free vitamin B12 is bound by the intrinsic factor (IF, a glycosylated protein secreted by gastric parietal cells) forming IF‐vitamin B12 complex, which is eventually absorbed in the ileum.…”
Section: Adverse Reactions In Clinical Application Of Metforminmentioning
confidence: 99%
“…Since 1971, when malabsorption of vitamin B12 in diabetic patients with metformin was first reported, 80 numerous clinical trials and meta‐analyses have confirmed the association between metformin and low vitamin B12 levels 81–87 . Vitamin B12 is found in foods as a protein‐binding form and released under the action of gastric acid pepsin and trypsin after entering the digestive tract.…”
Section: Adverse Reactions In Clinical Application Of Metforminmentioning
confidence: 99%
“…In all, one-fourth of the adult population is affected by DM, and the number is expected to more than quadruple by 2030. [ 1 2 3 4 5 ] The most concerning trend is the rise in DM prevalence in recent years, with a roughly tenfold increase in KSA during the previous30 years. [ 6 7 ] According to the World Health Organization, KSA has the second-highest DM rate in the Middle East and is seventh in the world.…”
Section: Introductionmentioning
confidence: 99%